The effect of semantic contrast on text interpretations in the exegesis of Al-Zamakhsharī - Hussein, Alhassan AbdurRahim (Journal of Arabic Language Sciences and Literature, 2023)
This paper investigates the role of semantic contrast in conveying the meanings of Quranic texts in Al-Zamakhsharī's exegesis, Al-Kashshāf. Semantic contrast is one of the major types of relationships that exist between the meaning of words, phrases or sentences. The study highlights the significance of semantic contrast and its impact on understanding Quranic texts. It also demonstrates to what extent semantic contrast influences the interpretation of texts in the context of Al-Zamakhsharī’s exegesis. Through a content analysis of samples from Al-Kashshāf, the study examines the effect of semantic contrast on the meanings of Quranic texts. The findings of the study confirm the presence of semantic contrast in individual words and structures in the Quran. Additionally, the study found that the relationship between opposing pairs can manifest as a contradiction, contrast, or divergence in both form and meaning or in meaning alone. Furthermore, it found that Al-Zamakhsharī does not consider semantic contrasts as mere stylistic embellishments but instead focuses on them to bring forth the hidden meanings of Quranic texts.
Keywords: Al-Zamakhshārī; Al-Kashshāf; Semantic Relationships; Semantic contrast; Opposing pairs